Cost and Trend Analysis of Sago Processed Businesses in North Luwu and Palopo City, South Sulawesi Province - Busthanul, Nurbaya; Heliawaty, Heliawaty; Bakri, Rasyidah; Syafiuddin, Masyhur; Syam, Siti Hardiyanti; Sabania, Hani; Rahmawaty, Nabilah (International Journal of Agriculture System, 2025)
This study investigates sago-based food processing businesses' cost structure, profitability, and sustainability trends in North Luwu and Palopo City, South Sulawesi, Indonesia. Despite sago’s strategic role as a traditional food and a climate-resilient crop, the industry faces declining raw material availability, low farmer income, and limited technological adoption. Using a combined qualitative-quantitative descriptive approach, including structured surveys and focus group discussions (FGDs), this research provides a detailed cost and trend analysis of micro and small- scale enterprises producing local sago foods such as bagea, dange, and kapurung. The findings reveal that while these businesses remain economically viable—with R/C ratios above 1.0 and the dange business reaching 2.1—profitability is constrained by small-scale operations, high input costs, and inadequate support systems. This study fills a critical research gap by shifting focus from upstream sago cultivation to downstream enterprise viability, offering a rare empirical insight into the dynamics of traditional food microenterprises in Indonesia. The novelty of this research lies in its integrated assessment of cost efficiency, scale potential, and policy implications. It proposes strategic interventions including modernizing processing technologies, strengthening farmer- producer linkages, and scaling up through cooperative models. The results provide actionable recommendations for local governments and agribusiness stakeholders aiming to revitalize indigenous food sectors. Future research should explore the design of sustainable enterprise clusters, examine consumer preferences for sago-based products, and evaluate the long-term impacts of technological and institutional interventions on sago industry resilience.